Functional traits and adaptive capacity of European forests to climate change - Bussotti, Filippo; Pollastrini, Martina; Holland, Vera; Brüggemann, Wolfgang (Environmental and Experimental Botany, 2014)
Increasing temperatures and drought risks through climate change are expected to have several consequences for European forests. Adaptive strategies may include: (i) persistence of the current forest types, thanks to the acclimatization to local conditions and to phenotypic plasticity of the populations; (ii) evolution, or local adaptation, i.e., change in genotype (frequencies) within the same species due to environmental pressure. It is favored by large within population diversity and (when possible) gene flow among populations; (iii) migration and substitution of species; and (iv) extinction of populations with low ecological plasticity, especially at the edges of their distribution or in the case of isolated (relict) populations. Because of the economic and ecological relevance of forests, it is of fundamental importance to apply appropriate forest management to make forests able to cope with the new environmental conditions. This may include changes in the composition and structure of forest stands, selection of adapted provenances of the most important European tree species or, if this is regarded as insufficient, assisted migration (i.e., the use of species suitable for the future climatic conditions) and, alternatively, substitution of native with non native species. The intraspecific (genetic and phenotypic) variability at a given site has been proven to be often higher than the variability among sites. Species with a large distribution range are supposed to have a wide variety of genotypes, allowing them to be adapted to different environmental conditions. Genetic variability and phenotypic plasticity are the key factors for the identification of useful tree genotypes for future forestation programs. Adaptation to drought, i.e., the probably most important future abiotic risk factor for forestry, can be reflected in variation of key functional traits (FT), at morphological, physiological and phenological level. FT utilized to screen for adapted genotypes in common gardens and provenance trials include growth, survival, leaf flushing and senescence, foliar features as leaf mass per area and nitrogen content, water use efficiency (e.g., estimated by analysis of the stable carbon isotopes, d13C) chlorophyll content, photosystem II functioning, and photosynthetic capacity under water shortage. Current modeled simulation of future forest distribution suggests the expansion of forests at the highest latitudes and altitudes, alongside with a reduction in the hottest and driest Mediterranean regions of South Europe. The general expectations, however, may be disproved especially at a regional level, by factors unexpected or not well known, such as possible extreme climatic events and increased roles of parasites/diseases (with negative effects), or high capacity of forest persistence or adaptation (with positive effects). Natural migration and species substitution can be hampered by co-factors of climate change, such as forest fragmentation and increased frequency and intensity of forest fires.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Adaptation; Extinction; functional traits; Local evolution; migration; Phenotypic plasticity; Phenotyping; provenances

Functional traits of cryptogams in Mediterranean ecosystems are driven by water, light and substrate interactions - Giordani, Paolo; Incerti, Guido; Rizzi, Guido; Rellini, Ivano; Nimis, Pier Luigi; Modenesi, Paolo (JOURNAL OF VEGETATION SCIENCE, 2014)
Question Poikilohydric organisms can survive desiccation without damage and recover soon after re-wetting. In this work we explore the realized niches of epilithic, poikilohydric organisms, i.e. lichenized and lichenicolous fungi and bryophytes, grouped into 15 functional guilds based on growth form, reproductive strategy and photosynthetic traits. We hypothesize that in Mediterranean ecosystems, the distribution of these guilds is controlled by water availability and solar radiation, together with characteristics of the substrate. Location Western Sardinia (Italy). The area hosts Mediterranean Quercus ilex forests on basaltic substrata within an agroforestry landscape. Methods The presence or absence of species from each guild was recorded in 1025 small quadrats (10x10cm). Four environmental variables were measured: solar radiation, microtopography (potential water run-off), substrate roughness and number of cracks. The occurrence of each guild was related to environmental variables using non-parametric multiplicative regression, and ecological niches of the guilds were derived from those models. Results The occurrence of all functional guilds varied significantly according to the selected environmental variables. In most cases, solar radiation was the most important variable; TI was included first in the model of two sorediate guilds, whereas four sexually reproducing functional guilds had surface relief as first variable. The growth forms were separated along a gradient of increasing solar radiation, whereas water run-off and surface roughness mainly discriminated reproductive strategies and photobionts. Vegetatively reproducing guilds with other photobionts than Euphyta-like pigments were confined to the border of the ecological space, defined by gradients of environmental factors, which was largely occupied by more competitive, sexually reproducing organisms. Conclusions Functional traits of epilithic poikilohydric organisms were associated with ecological adaptations to the stressful environment of Mediterranean outcrops. We showed that their response in terms of probability of occurrence is coherent with quantitative gradients of solar radiation and water availability at the micro-scale.
Keywords: bryophytes; functional traits; lichens; Photosynthetic strategy; Reproductive strategy

Functional traits predict drought performance and distribution of Mediterranean woody species - Lopez-Iglesias, Bárbara; Villar, Rafael; Poorter, Lourens (Acta Oecologica, 2014)
Water availability is one of the key environmental factors that affect plant establishment and distribution. In many regions water availability will decline with climate change, exposing small seedlings to a greater likelihood of drought. In this study, 17 leaves, stem, root, and whole-plant traits of ten woody Mediterranean species were measured under favourable growing conditions and seedling drought survival was evaluated during a simulated dry-down episode. The aims of this study were: i) to assess drought survival of different species, ii) to analyse which functional traits predict drought survival time, and iii) to explain species distribution in the field, based on species drought survival and drought strategies. Drought survival time varied ten-fold across species, from 19 to 192 days. Across species, drought survival was positively related to the rooting depth per leaf area, i.e., the ability to acquire water from deeper soil layers while reducing transpiring leaf area. Drought survival time was negatively related to species ability to grow quickly, as indicated by high relative growth and net assimilation rates. Drought survival also explained species distribution in the field. It was found that species were sorted along a continuum, ranging between two contrasting species functional extremes based on functional traits and drought performance. One extreme consisted of acquisitive fast-growing deciduous species, with thin, soft metabolically active leaves, with high resource use and vulnerability to drought. The opposite extreme consisted of conservative slow-growing evergreen species with sclerophyllous leaves, deep roots, a low transpiring area, and low water use, resulting in high drought survival and drought tolerance. The results show that these drought strategies shape species distribution in this Mediterranean area.
Keywords: Drought; Functional groups; functional traits; mediterranean species; RGR; Rooting depth

Alleviation of Zn toxicity by low water availability - Disante, Karen B; Cortina, Jordi; Vilagrosa, Alberto; Fuentes, David; Hernández, Encarni I; Ljung, Karin (Physiologia Plantarum, 2013)
Heavy metal contamination and drought are expected to increase in large areas worldwide. However, their combined effect on plant performance has been scantly analyzed. This study examines the effect of Zn supply at different water availabilities on morpho-physiological traits of Quercus suber L. in order to analyze the combined effects of both stresses. Seedlings were treated with four levels of zinc from 3 to 150 µM and exposed to low watering (LW) or high watering (HW) frequency in hydroponic culture, using a growth chamber. Under both watering regimes, Zn concentration in leaves and roots increased with Zn increment in nutrient solution. Nevertheless, at the highest Zn doses, Zn tissue concentrations were almost twice in HW than in LW seedlings. Functional traits as leaf photosynthetic rate and root hydraulic conductivity, and morphological traits as root length and root biomass decreased significantly in response to Zn supply. Auxin levels increased with Zn concentrations, suggesting the involvement of this phytohormone in the seedling response to this element. LW seedlings exposed to 150 µM Zn showed higher root length and root biomass than HW seedlings exposed to the same Zn dose. Our results suggest that low water availability could mitigate Zn toxicity by limiting internal accumulation. Morphological traits involved in the response to both stresses probably contributed to this response.
APS
Keywords: Drought; functional traits; Heavy metals; Quercus suber L.

Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M.; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M.; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

Drove roads as local biodiversity reservoirs: effects on landscape pattern and plant communities in a Mediterranean region - Azcárate, Francisco M.; Robleño, Irene; Seoane, Javier; Manzano, Pablo; Peco, Begoña (Applied Vegetation Science, 2012)
Question: What are the effects of traditional drove roads on landscape pattern and plant communities? Location: Madrid Autonomous Region, Central Spain. Methods: We selected four study localities in different landscape units. Within each locality, we selected eight sites and within each site, we established three 1-ha plots, each corresponding to one of three situations: drove road, adjacent matrix or distant matrix. The landscape pattern of each plot was characterized by the cover of the different patch types, the patch type richness ha 1 and the patch type evenness ha 1 . At one site per locality, we also recorded vegetation by randomly distributing twenty 20 cm 9 20 cm quadrats per plot. We characterized each quadrat by its species richness, plant species composition and plant functional composition. We also analysed species richness by constructing rarefaction curves for each plot. Results: In the localities situated in croplands, sub-mediterranean forests and coniferous forests, drove roads were found to be an important source of spatial heterogeneity and a reservoir for a large number of plant species. In contrast, drove roads did not differ from the matrix habitats in rangelands, suggesting that the processes shaping drove road vegetation are similar to the general processes that shape grazed systems. Drove roads did not imply a signiﬁcant increase in functional diversity. Our results were heavily scale-dependent: while drove roads provided heterogeneity at the local scale, they showed a remarkable similarity at the large scale. Conclusions: Drove roads act as authentic local biodiversity reservoirs, especially in environments with low grazing levels. At the same time, drove roads imply structural and functional continuity on a large scale, increasing potential connectivity at the regional level. We recommend the preservation of drove roads in a functional state, because of their beneﬁts to plant biodiversity conservation, and claim that these beneﬁts should be considered when designing livestock policies with different intensiﬁcation scenarios.
Keywords: extensive grazing; functional diversity; functional traits; landscape heterogeneity; Transhumance

Relationships between leaf morphological traits, nutrient concentrations and isotopic signatures for Mediterranean woody plant species and communities - Domínguez, María T.; Aponte, Cristina; Pérez-Ramos, Ignacio M.; García, Luis V.; Villar, Rafael; Marañón, Teodoro (Plant and Soil, 2012)
Background and aims Soil factors are driving forces that influence spatial distribution and functional traits of plant species. We test whether two anchor morphological traits—leaf mass per area (LMA) and leaf dry matter content (LDMC)—are significantly related to a broad range of leaf nutrient concentrations in Mediterranean woody plant species. We also explore the main environmental filters (light availability, soil moisture and soil nutrients) that determine the patterns of these functional traits in a forest stand. Methods Four morphological and 19 chemical leaf traits (macronutrients and trace elements and δ 13 C and δ 15 N signatures) were analysed in 17 woody plant species. Community-weighted leaf traits were calculated for 57 plots within the forest. Links between LMA, LDMC and other leaf traits were analysed at the species and the community level using standardised major axis (SMA) regressions Results LMA and LDMC were significantly related to many leaf nutrient concentrations, but only when using abundance-weighted values at community level. Among-traits links were much weaker for the crossspecies analysis. Nitrogen isotopic signatures were useful to understand different resource-use strategies. Community-weighted LMA and LDMC were negatively related to light availability, contrary to what was expected. Conclusion Community leaf traits have parallel shifts along the environmental factors that determine the community assembly, even though they are weakly related across individual taxa. Light availability is the main environmental factor determining this convergence of the community leaf traits.
Keywords: Community weighted means; functional traits; isotopes; leaf dry matter content; Leaf mass per area; macronutrients; Specific leaf area

Functional response traits in relation to land use change in the Montado - Castro, Helena; Lehsten, Veiko; Lavorel, Sandra; Freitas, Helena (Agriculture, Ecosystems & Environment, 2010)
The socio-economic changes of the last decades have resulted in changes in traditional land uses with consequent abandonment of large farmland areas in the Mediterranean region. We assessed the response of species richness and composition, and species functional traits to decreasing land use intensity in a Montado system, an agro-pastoral system characteristic of the Alentejo, Southern Portugal. Additionally, we investigated whether plant functional types can be established based on the response to decreasing land use intensity in these systems. Consistent with previous studies, species richness decreased sharply after land abandonment, and this was associated with a strong turnover in species composition from grazed to abandoned sites as the vegetation changed from herbaceous to shrub dominated communities. Pronounced differences in functional traits were found for different successional stages. Therophyte life form, short plant height, high speciﬁc leaf area (SLA), low leaf dry matter content (LDMC) and small seeds with dispersal structures were dominant in grazed plots. Within abandoned plots, chamaephytes dominated in plots abandoned for 10–15 years and decreased in favour of nanophanerophytes in plots abandoned for 20–30 years. Plant height, LDMC and seed mass increased with abandonment time while SLA decreased. Functional response groups sufﬁcient to describe vegetation change were identiﬁed combining life form and SLA. Therophytes with medium SLA were the dominant functional group in grazed areas, while nanophanerophytes with medium or low SLA were associated with later phases of abandonment. At intermediate stages of succession the dominant group was chamaephytes with medium SLA but functional diversity was highest as all the groups, except hemicryptophytes with medium SLA, were represented. These changes in functional composition can be translated into effects on key ecosystem properties. The increase in LDMC indicates an increase in ﬂammability while trends in both LDMC and SLA suggest decreased decomposition, and thereby carbon and nutrient cycling. These will need to be considered in combination with consequences for other ecosystem properties for future management.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Fourth-corner method; Functional groups; functional traits; Mediterranean; Null model; Plant; Secondary succession

Ecophysiological Traits Associated with Drought in Mediterranean Tree Seedlings: Individual Responses versus Interspecific Trends in Eleven Species - Valladares, F; Sánchez-Gómez, D (Plant Biology, 2006)
Abstract: Species differ regarding their drought tolerance and individuals of a given species can modify their morphology and physiology in response to drought. However, since evolutionary and ecological selective pressures differ, individual and interspecific responses to drought might not match. We determined summer survival and a number of ecophysiological variables in two factorial experiments with seedlings of eleven tree species present in Mediterranean ecosystems, grown under slowly imposed water stress and control conditions. Plants experiencing drought exhibited reduced growth, low specific leaf area, chlorophyll content, and photosynthetic rate when compared to the controls, and species-specific drought tolerance was associated with an analogous set of trait values. However, while species with high leaf area ratio and shoot-root ratio exhibited greater drought tolerance, drought induced the reversed response within species. Contrary to expectations, water use efficiency was lower in drought-tolerant species and decreased in water-stressed individuals compared to the control plants. There was a distinctive phylogenetic signal in the functional grouping of species, with oaks, pines, and other genera being clearly different from each other in their drought tolerance and in their functional responses to drought. However, all relationships between ecophysiological variables and drought tolerance were significant after accounting for phylogenetic effects, with the exception of the relationship between drought tolerance and photochemical efficiency. Our results show that drought tolerance is not achieved by a single combination of trait values, and that even though evolutionary processes and individual responses tend to render similar results in terms of functional traits associated with drought, they do not necessarily match.
Keywords: Drought tolerance; functional traits; Mediterranean plants; phylogeny; water use efficiency; woody seedlings

Ecophysiological Traits Associated with Drought in Mediterranean Tree Seedlings: Individual Responses versus Interspecific Trends in Eleven Species - Valladares, F.; Sánchez-Gómez, D. (Plant Biology, 2006)
Abstract: Species differ regarding their drought tolerance and individuals of a given species can modify their morphology and physiology in response to drought. However, since evolutionary and ecological selective pressures differ, individual and interspecific responses to drought might not match. We determined summer survival and a number of ecophysiological variables in two factorial experiments with seedlings of eleven tree species present in Mediterranean ecosystems, grown under slowly imposed water stress and control conditions. Plants experiencing drought exhibited reduced growth, low specific leaf area, chlorophyll content, and photosynthetic rate when compared to the controls, and species-specific drought tolerance was associated with an analogous set of trait values. However, while species with high leaf area ratio and shoot-root ratio exhibited greater drought tolerance, drought induced the reversed response within species. Contrary to expectations, water use efficiency was lower in drought-tolerant species and decreased in water-stressed individuals compared to the control plants. There was a distinctive phylogenetic signal in the functional grouping of species, with oaks, pines, and other genera being clearly different from each other in their drought tolerance and in their functional responses to drought. However, all relationships between ecophysiological variables and drought tolerance were significant after accounting for phylogenetic effects, with the exception of the relationship between drought tolerance and photochemical efficiency. Our results show that drought tolerance is not achieved by a single combination of trait values, and that even though evolutionary processes and individual responses tend to render similar results in terms of functional traits associated with drought, they do not necessarily match.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought tolerance; functional traits; Mediterranean plants; phylogeny; water use efficiency; woody seedlings